Dentoalveolar infection: clinico pathological case - Witjaksono, Widowati (2013)
The dental abscess is a difficulty of decay of the tooth. It can also be caused by tooth trauma when a tooth is chipped or broken. Any opening in the enamel of the tooth lets bacteria in to cause an infection of the tooth center known as the pulp. The infection can spread from the tooth root and into the bones which support the tooth. Bacteria from dental caries (a tooth cavity) can extend into the gums, the cheek, the throat, beneath the tongue, or even into the jaw or facial bones. A dental abscess can become very painful when tissues become inflamed or due to the pressure within the abscess. A gum or gingival abscess is the result of infection or trauma to the surface of the gum tissue. Periodontal abscesses are the result of an infection that has moved deeper into gum areas, and a periapical abscess refers to a tooth with an infection of the pulp. The success of both periodontal and periapical abscesses therapy depends on the elimination of both disease processes, whether they exist separately or as a combined lesion. Diagnosis is paramount to determining the course of treatment and overall prognosis This paper aims at presenting a comprehensive review of several aspects of periodontal and periapical lesions.